EFEK HEPATOPROTEKTIF EKSTRAK TEH HIJAU(Camellia sinensis) PADA TIKUS PUTIH (Rattus norvegicus) YANG DIINDUKSI ALOKSAN - Muhammad Hafizh Hammami (2020)
Diabetes mellitus triggers an increase free radicals from increased glucose oxidation through polyol pathway, which trigger oxidative stress and cause liver damage. Green tea contains polyphenol which is hepatoprotective. This study aims to determine the effectiveness of green tea extract to decrease SGPT and SGOT blood levels in white rats alloxan-induced. Sample was 30 male white rats wistar strain, aged 8-12 weeks, weight 150-200 g and grouped (K1) control group, (K2) rats alloxan-induced group, (K3) rats alloxan-induced and green tea extract 100 mg/kgBW group, (K4) rats alloxant-induced and green tea extract 200 mg/kgBW, (K5) rats alloxant-induced and green tea extract 400 mg/kgBW. After 3 days administration alloxan 125 mg/kgBW, given treatment for 16 days. Rats were terminated using ketamine were given intramuscularly, then dissected and taken blood plasma then measurement of SGOT and SGPT plasma levels using spectrophotometer with wavelength of 340 nm. One Way Anova test, there was an effect of giving green tea extract on plasma SGPT (p=0,005) and SGOT (p=0,002) levels. Post Hoc Bonferroni test, adimistration of green tea extract 100 mg/kgBW can reduce plasma SGPT (p=0,02) and SGOT (p=0,004) close to normal values. Conclusion: green tea extract 100 mg/kgBW has hepatoprotective effect in alloxan-induced white rat.